fitball: Una forma diferente y divertida para mejorar nuestra salud - Moral Moreno, Luis (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2002)
Boys and girls, young and Elder people perform physical exercises with a giant ball, all of them properly dressed and following the rhythm of music. This activity is a variant of fitness invented in California at the end of the 80's and beginning of the 90's. The conditioning programmes with giant balls ( Fitball, Swiss Ball….) are being used by all kind of people to improve equilibrium, strength, coordination, position, back care and cardiovascular health. This practice becomes a very useful tool for many sports, leisure activities, PE lessons and even sedentary lifestyle as promoters of an active alternative seat instead of traditional chairs, due to the mobility, the interest and the amusement it cause.